Development of the Personal Site of a Modern Scientist - Вячеслав Осадчий (Ukrainian Journal of Educational Studies and Information Technology, 2018)
The article is devoted to the actual and practically important problem for modern science - to provide free access to the scientific creative heritage of the scientist. After all, the weight of the scientist in the professional community, his influence on the events occurring in his chosen field of science, today largely depends on how fully, constructively and organically presented the results of his research on the Internet. The central element of a visiting card of a modern scientist is a link to a personal website. Keeping your own site allows you to create an electronic library of scientific and methodological developments, share your thoughts, finds. In addition, the creation and maintenance of their site contributes to replenishing the portfolio of achievements of the scientist. The authors proceed from the basic provision that the personal page as a form of information provision in the scientific community gives scientists and specialists new opportunities for solving scientific and practical problems. The materials of the scientist, presented on the site, allow to show the level of erudition in the branches of science and culture, help to achieve public recognition.